2010
DOI: 10.2139/ssrn.1717224
|View full text |Cite
|
Sign up to set email alerts
|

Individualism, Uncertainty Avoidance, and Earnings Momentum in International Markets

Abstract: The literature shows that price and earnings momentum returns cannot be fully explained by risk-based theories. In an attempt to better understand the price momentum anomaly, Chui et al. [2010] document that the cultural factor of-individualism‖ influences price momentum returns, but that the cultural factor of-uncertainty avoidance‖ does not. The current study extends Chui et al. [2010] by examining the influence of individualism and uncertainty avoidance on earnings momentum profits, as theory suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 80 publications
0
23
0
Order By: Relevance
“…Our motivation to focus on the investors’ perspective stems from the rich literature in behavioral finance documenting the relevance of investor characteristics and biases to asset pricing. For example, prior literature documents that investor traits influence investment choice, trading volume, volatility, returns, and level of cash holdings (e.g., Grinblatt and Keloharju, ; Barberis and Shleifer, ; Gaspar et al., ; Kumar, ; Chui et al., ; Neamtiu et al., ; Hirshleifer, 2015; and Dou et al., ). Differences in national cultural characteristics present an opportunity to examine the effect of investors’ cultural traits on firm (and cash) valuation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our motivation to focus on the investors’ perspective stems from the rich literature in behavioral finance documenting the relevance of investor characteristics and biases to asset pricing. For example, prior literature documents that investor traits influence investment choice, trading volume, volatility, returns, and level of cash holdings (e.g., Grinblatt and Keloharju, ; Barberis and Shleifer, ; Gaspar et al., ; Kumar, ; Chui et al., ; Neamtiu et al., ; Hirshleifer, 2015; and Dou et al., ). Differences in national cultural characteristics present an opportunity to examine the effect of investors’ cultural traits on firm (and cash) valuation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these factors have been shown to affect a number of other corporate decisions and asset pricing attributes. Individualism is shown to influence corporate investments (Shao et al., 2010), momentum (Chui et al., ), corporate debt maturity (Zheng et al., ), earnings momentum profit (Dou et al., ), investors’ risk preferences (Rieger et al., ), post‐acquisition performance (Chakrabarti et al., 2009), and M&A activity (Ferris et al., ). Uncertainty avoidance is shown to have an effect on corporate debt maturity (Zheng et al., ), investors’ risk preferences (Rieger et al., ), and leverage decisions (Wang and Esqueda, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while there is a clear split between western and ESEA markets for momentum, the picture is mixed for earnings momentum. Nonetheless, as Dou et al () show, culture is clearly related to PEAD, as it has been shown to be for momentum by Chui et al ().…”
Section: Introductionmentioning
confidence: 91%
“…Similarly, in relation to earnings momentum, Hong et al () examine 11 markets and find significant profits for all of the western markets in their sample and only one (Hong Kong) of six ESEA markets. However, while Dou et al () find a significant relationship between zero‐investment earnings momentum strategies and culture, they find significant positive returns for most of the major western and ESEA markets (the exception being Singapore, where returns are insignificantly different from zero). Thus, while there is a clear split between western and ESEA markets for momentum, the picture is mixed for earnings momentum.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation